2009
DOI: 10.1136/bcr.09.2008.0897
|View full text |Cite
|
Sign up to set email alerts
|

An elderly woman with Prevotella bacteraemia secondary to pyometra

Abstract: An 87-year-old woman was admitted to our hospital with sepsis and foetid vaginal discharge. She presented an abdominal mass that had been present for the last 20 years, refused diagnostic or therapeutic procedures. A computed tomography scan detected a uterine body with multiple calcifications and an internal collection of 10 cm. No other infectious sources were apparent. A tentative diagnostic of pyometra was made and empiric antibiotic treatment was initiated. A hysteroscopy was performed with incomplete dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
(5 reference statements)
0
2
0
1
Order By: Relevance
“…Guerrero et al (2009) reported a case of an elderly woman with pyometra; she had noted a mass in her abdomen 20 years previously, but had at that point decided against any medical assessment. She was referred to a hospital with a painful mass and a simple abdominal x-ray showed a lower abdominal mass with multiple calcifications (Guerrero et al 2009). We suggest that these radiographic opacities might have been due to the open condition of the cervix and the chronic process of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guerrero et al (2009) reported a case of an elderly woman with pyometra; she had noted a mass in her abdomen 20 years previously, but had at that point decided against any medical assessment. She was referred to a hospital with a painful mass and a simple abdominal x-ray showed a lower abdominal mass with multiple calcifications (Guerrero et al 2009). We suggest that these radiographic opacities might have been due to the open condition of the cervix and the chronic process of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Munson et al described a case of a tiger with severe endometrial mineralisation revealed by radiographs (Munson et al 2002). Guerrero et al (2009) reported a case of an elderly woman with pyometra; she had noted a mass in her abdomen 20 years previously, but had at that point decided against any medical assessment. She was referred to a hospital with a painful mass and a simple abdominal x-ray showed a lower abdominal mass with multiple calcifications (Guerrero et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Siempre con cobertura antibiótica de amplio espectro y posterior seguimiento para evitar recurrencias. La rotura de la piómetra debe ser tenida en cuenta en caso de mujeres ancianas con abdomen agudo 1,3,10 . Sería adecuado analizar series de casos prospectivamente 8 .…”
Section: Conclusiónunclassified